An analysis of the intergenerational family economic support expectations and responsibilities amongts black South African employed graduates : implications for social work practice - Mafa, Prudence (My University, 2024)
The practice of providing support to kin is an activity which has been passed down through generations amongst black people. This was done to ensure that the needs of individual members and those of a family as a whole are catered for by the family. This current study sought to explore and describe the socio-economic merits and limitations of economic support provision in black families. These are the objectives which made it possible for the study aim to be achieved: to identify determinants of economic intergenerational support provision; to determine how economic support is utilised in the family; to appraise benefactors’ experiences with regards to providing economic support to family members; to assess the impact of economic intergenerational support on family dynamics; and lastly to formulate strategies to ease the burden experienced by graduates who provide economic support to their intergenerational families. The study was done so that the phenomenon of intergenerational economic support provision could be analysed with social work lenses as it has social implications on the lives of both benefactors and their beneficiaries. The social work profession is committed to alleviating human suffering in all its forms. As such, this study was able to illuminate socio-economical burdens and benefits associated with intergenerational economic support and recommended ways to mitigate discomforts brought by this phenomenon. This study employed a phenomenological approach to study the essence of intergenerational economic support in black families and to find out what this phenomenon means to the participants. This was a qualitative, exploratory descriptive study in which data was collected by means of individual interviews. Interviews were held with ten employed black South African University graduates who were providing economic support to their extended family members. these participants were from the following provinces: Limpopo, Mpumalanga, Gauteng, North West, KwaZulu-Natal, and Free State. Data was presented according to the themes which emerged during the data analysis process. The study findings revealed that intergenerational economic support is a complex and multi-layered issue. It was found to be a personal, family, and structural problem which could persist for generations to come if the family and environmental circumstances do not change. This proposed study therefore proposes a family centred programme on the intergenerational family economic support provision to help ease the burden of support provision.
Thesis (Ph.D. (Social Work)) -- University of Limpopo, 2024
Keywords: Intergenerational economic support; University graduates; Social work; South Africa; Family economic support provision; Black families; Intergenerational relations; Families, Black; Families; College graduates, Black